Electroencephalographic Signs Characteristic for Without Several Epileptic Encephalopathy in Preschool Children (The Peerian Journal, 2022)
Epileptic encephalopathy is a condition when a pathological altered brainelectrogenesis is the cause of impaired brain function [5,6]. The epileptic process leads toprogressive impairment of brain functions. According to the literature, these disorders dependon the form of 5 to 40% of behavioral, mental and neuropsychological disorders [2,4,8,9].Currently, some researchers consider interictal epileptic psychoses as a manifestation ofepileptic encephalopathy. Epileptic encephalopathy is a condition where pathologically alteredbrain electrogenesis is the cause of brain dysfunctions. In which the epileptic process as suchleads to progressive dysfunctions of the brain